MICROELEMENT COMPOSITION OF POTABLE GROUNDWATER IN KOROSTYSHIV DISTRICT OF ZHYTOMYR REGION IN HYDROGEOCHEMICAL MONITORING SYSTEM - Koshliakova, T.; Kuraieva, І.; Koshliakov, О.; Oleksenko, L.; Shvaika, І.; Proskurka, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is devoted to the study of microelement composition of potable groundwater in Korostyshiv district of Zhytomyr region in terms of potential threats to human health. The study was conducted as part of general monitoring studies set of groundwater quality in the region in July 2020 – August 2021. Microelement analysis of water samples was performed by use of modern highly sensitive method of mass spectrometry with inductively coupled plasma (ICP-MS). The results obtained may be useful to justify the need to adjust the diet of local residents through the additional use of vitamin and mineral complexes.
Keywords: potable groundwater; microelement composition; hydrogeochemistry; monitoring; essential elements; technogenic influence